Man: Ratio of Natural and Social Origins - Krakauskas, Edmundas (Problemos, 1989)
The traditional interpretation of man as a bio-social being is put under question in the paper. The peculiarity of man is viewed in his consciousness. Therefore, from the point of view of man’s specific, i.e., human functioning, man is characterised as a spiritual being. Finally, reservations are made against possible evaluations of the standpoint as being an idealistic one.